The influence of the use of biological preparations on the formation of quality indicators of spring wheat grain - A. V. Nechaeva; S. V. Zharkova (Овощи России, 2023)
Relevance. For a more complete realization of the biological potential inherent in the culture and directly in each variety, in the agrotechnology used, separate elements are used that contribute to more effective plant development. This should include the use of biological preparations that are not only able to stimulate and regulate the growth and development of plants, but are also safe for the environment. In this regard, the research results presented in this paper are relevant and timely.Materials and methods. In our study, we studied the effect of pre-sowing treatment of spring wheat seeds and its (processing) aftereffect on grain quality indicators and seed sowing properties. The early-ripening variety of spring soft wheat Iren was taken as an object of research. The subject of the study is biological preparations, their effect and aftereffect during pre–sowing seed treatment on the formation of grain and the quality of the seed material of the crop.Results. Studies have revealed differences in the intensity of the effect of presowing seed treatment with biological preparations and the aftereffect of treatment on the quality indicators of spring wheat grain. The aftereffect of the drugs increased the protein content in the grain. The maximum protein content in the experiment was obtained in variant 2 (the preparation was obtained by the method of VAG based on pine needles (HS 22)) – 17.0%.The gluten content in the grain in variants of experiments 2 and 3 was formed above 32%, which corresponds to the 1st class. The maximum gluten content in the grain was obtained in variant 2 (HS 22) – 41.8% in experiment 3 (aftereffect). The vitreous content of the grain in all variants of experiments 2 and 3 is higher than 60%, which makes it possible to classify the grain to the 1st class. A higher level of grain nature was obtained on variants with the aftereffect of drugs. Grain on the variants of experiment 3: control, 3 (LP 4), 8 (Cytohumate), 9 (Lignohumate) with grain in kind above 750 g should be attributed to the 1st class.